Melatonin-induced physiology and transcriptome changes in banana seedlings under salt stress conditions - Wei, Junya; Liang, Jinhao; Liu, Debing; Liu, Yuewei; Liu, Guoyin; Wei, Shouxing (Frontiers in Plant Science, 2022)
Soil salinization is one of the most common abiotic stresses in agricultural production worldwide which poses a serious threat to the ecological environment and agricultural production. Banana (Musa acuminata L.) is a salt sensitive plant that growth, development, and production is constrained by salt stresses. Melatonin is known to improve the resistance of plants to stress. In this study we analyzed the phenotypic, physiological and transcriptome changes of a main agriculture banana variety (Musa acuminata cv. BD) with 100 mM melatonin under salt stress condition. The phenotypic results showed that the application of 100 μM exogenous melatonin could maintain banana plants health growth and alleviate the damage caused by salt stress. The physiological data show that the application of exogenous MT can resist salt stress by increasing the content of soluble sugar and soluble protein, slowing down the degradation of chlorophyll, improving membrane permeability, enhancing root activity, reducing the accumulation of MDA and enhancing antioxidant defense activity of BD banana plant. Transcriptome sequencing analysis result suggested that the melatonin-induced salt resistance involved in the process of biological process, molecular function and cellular component in BD banana seedlings. We also found the DEGs involved in multiple metabolic pathways that were significantly enriched, including Amino sugar and nucleotide sugar metabolism, Phenylalanine metabolism, cyanoamino acid metabolism, starch and sucrose metabolism and Linoleic acid metabolism and these major metabolism and biosynthesis may participate in the underlying mechanisms of melatonin in salt stress. Furthermore, some transcription factor family members genes consist of MYB, NAC, bHLH and WRKY might contribute to melatonin alleviates salt stress tolerance of BD banana plant. The results of this study laid a foundation for further clarifying the mechanism of salt stress resistance of banana mediated by exogenous melatonin and provide theoretical bases to utilize melatonin to improve banana salt tolerance in the future.